Antimicrobial Activity of Mixed Lactobacilli in Combination with Antibiotics Against Bacterial Pathogens Causing Chronic Suppurative Otitis Media - Shireen Moyaed Jassim, Ammar Algburi, (Pakistan Journal of Medical & Health Sciences, 2022)
This study aimed to determine the antimicrobial activity of CFS of the selected lactobacilli, alone and in combination with antibiotics against pathogenic bacteria isolated from patients with chronic otitis media. In addition, we investigated the ability of tested lactobacilli (a mixed of Lactobacillus acidophilus and Lactobacillus plantarum) to co-aggregate with the isolated pathogens.. One hundred sixty-two ear swab were collected from patients had otitis media with chronic discharging . These patients attended to the ENT department in the medical consultation clinic at Baquba Teaching Hospital and to private doctors’ clinics. Ear swabs were taken from both sexes, male and female starting from September to the end of December, 2021. The isolates were identified based on their morphological features of the colonies and some biochemical tests. The final identification and antibiotics susceptibility of bacterial isolates was confirmed by VITEK2 compact system. The results showed that 113 samples were positive for bacterial culture, while 30 samples were negative growth, mostly identified as fungi. A total of 113 bacterial species isolated from 162 otitis media samples were: Pseudomonas aeruginosa, Staphylococcus aureus, Proteus mirabilis, and Klebsiella pneumonia. The highest predominant bacterial agents were P. aeruginosa 52 (32%), S. aureus 40 (24.7%), followed by P. mirabilis 14 (8.64%), and K. pneumoniae 7 (4.32%). The obtained results showed that the highest rate of infection was identified in male rather than in female. In antibiotic susceptibility testing, 16 types of antibiotics was evaluated against four bacterial species using VITEK2 system. In addition, disk diffusion assay was utilized in order to perform antimicrobial combinations. The susceptibility of bacterial species were various among these antibiotics. It was noticed that ciprofloxacin was the most effective antibiotic against all the isolated bacteria with the lowest MIC in comparison to the other antibiotics. We evaluated the effect of ciprofloxacin alone and in combination with the cell-free supernatants (CFSs) of mixed lactobacilli against the four isolates using disk diffusion assay. Our results showed that the CFS produced by the mixed lactobacilli have a significant inhibitory effect on the growth of bacterial pathogens. Moreover, CFS in combination with ciprofloxacin was more effective against pathogenic isolates than using ciprofloxacin alone. Co-aggregation of the selected mixed lactobacilli strains with the four bacterial isolates were evaluated in order to investigate the competitive activity of the tested lactobacilli with the isolated pathogens.